VD_FINDINFO HC / 2016 / 410 vom 20. April 2016 - VD Tribunal cantonal (2016)
OBLIGATION D'ENTRETIEN, ENFANT, MODIFICATIONEN GÉNÉRAL, REVENU D'UNE ACTIVITÉ LUCRATIVE INDÉPENDANTE | 176 CC, 286 al. 2 CC